The Impact of Syrian Refugees on the Labor Market in Neighboring Countries: Empirical Evidence from Jordan - Ali Fakih; May Ibrahim (Institute for the Study of Labor (IZA), 2016)
This paper analyzes time-sensitive data on a humanitarian crisis in the Middle East. It aims to assess the impact of the steep influx of Syrian refugees into Jordan on the country's labor market since the onset of the conflict in Syria (March 2011). As of August 2014, nearly 3 million registered Syrians have sought refuge in neighboring countries (Lebanon, Jordan, Iraq, and Turkey), according to the United Nations High Commissioner for Refugees (UNHCR). Jordan and Lebanon are hosting the majority of them. This paper utilizes data regarding unemployment rates, employment rates, labor force participation, the number of refugees, and economic activity at the level of governorates. The Vector Autoregressive (VAR) methodology is used to examine time series data from the most affected governorates in Jordan. The empirical results of Granger causality tests and impulse response functions show that there is no relationship between the influx of Syrian refugees and the Jordanian labor market. Our results are verified through a set of robustness checks.
Keywords: J61; H56; N45; 330; forced refugees; host country; labor market; VAR model